دوافع ممارسة الأنشطة البدنية والرياضية في حصة التربية البدنية والرياضية لدى الإناث في الطور الثانوي. - بعبوش, بلال (My University, 2021)
هدف هذه الدراسة لمعرفة مدى وجود فروق بين الإناث في بعض الثانويات لولاية قسنطينة, حول دافعيتهن في ممارسة الأنشطة البدنية والرياضية في حصة التربية البدنية والرياضية من خلال دراسة ثلاث محاور أساسية للدافعية الرياضية ( دوافع الصيفات البدنية , دوافع الميول الرياضي, دوافع نفسية وعقلية), وقد تم إختيار هذا الموضوع لدراسته إنطلاقا من الظاهرة الغريبة التي أصبحت سائدة في الثانويات ألا وهي عزوف الإناث عن ممارسة التربية البدنية والرياضية. وقد إعتمدنا في هذه الدراسة على إستمارة إستبيان تحتوي على 30 سؤال تم توزيعها على اللإناث يدرسن في الطور الثانوي لولاية قسنطينة وقد بلغ عددهم 120 تلميذة موزعين على 7 ثانويات. وبعد جمع المعلومات وتحليلها إحصائيا فقد تبين لنا جليا بأنه لاتوجد فروق ذات دلالة إحصائية بين إجابات الإناث حول دافعيتهن للممارسة الأنشطة البدنية والرياضية من جانب اللياقة البدنية و كذلك ميولهن الرياضي, وحتى دوافعهن النفسية والعقلية.The aim of this study is to find out the extent to which there are differences between females in some secondary schools of the Wilayat of Constantine, about their motivation in practicing physical and sports activities in the physical education and sports class by studying three main axes of sports motivation (the motives of physical summers, the motives of sports tendencies, psychological and mental motives). This topic was chosen for study based on the strange phenomenon that has become prevalent in high schools, namely the reluctance of females to practice physical education and sports. In this study, we relied on a questionnaire form containing 30 questions that were distributed to females studying in the secondary phase of the Wilayat of Constantine, and their number reached 120 students distributed in 7 secondary schools. After collecting the information and analyzing it statistically, it became clear to us that there are no statistically significant differences between the responses of females about their motivation to practice physical and sports activities on the part of physical fitness, as well as their athletic tendencies, and even their psychological and mental motives.
The motives for practicing physical activities in the physical education and sports class of females in the secondary stage
مقال
Keywords: الدافعية، الأنشطة البدنية، حصة التربية البدنية والرياضية.; motivation; physical activities; physical education and sports class..